Aerobic reserve capacity in multiple sclerosis—Preliminary evidence. (29th April 2021) - Feasel, Corey D.; Sandroff, Brian M.; Motl, Robert W.
Abstract : Objectives: Aerobic reserve capacity reflects the available energy for performing everyday life tasks, and it has been studied in older adult populations. This preliminary study examined proof of concept and measurement of aerobic reserve capacity in multiple sclerosis (MS). Materials & Methods: Twenty‐one fully ambulatory people with MS performed a maximal, cardiopulmonary exercise test (CPET). We calculated aerobic reserve capacity based on the difference between peak aerobic power (VO2peak ) and first stage oxygen consumption (VO2 ). Participants completed assessments for disability (Expanded Disability Status Scale, EDSS), cognition (Symbol Digit Modalities Test, SDMT), mood (Beck Depression Inventory, BDI), walking endurance (six‐minute walk distance, 6MWD), walking speed (Timed Twenty‐Foot Walk, T25FW), impact of MS (Multiple Sclerosis Impact Scale, MSIS‐29), and anthropometric measurements (height and weight). Results: Aerobic reserve capacity was 9.3 ± 3.7 ml/kg/min. Aerobic reserve capacity was positively associated with VO2peak ( ρ  = .67, p  < .01), time to exhaustion ( ρ  = .63, p  < .01), and SDMT ( ρ  = .51, p  < .05). Aerobic reserve capacity was negatively associated with BMI ( ρ  = −.62, p  < .01) and RHR ( ρ  = −0.47, p  < .05). Conclusion: We provide preliminary evidence that aerobic reserve capacity is a feasible outcome derived from maximal CPET (eg, modified Balke protocol) in MS. Aerobic reserve capacity was associated with clinically relevant outcomes and could become an important outcome for rehabilitation in future research.